(untitled) (Communications in Mathematical Research, 2019)
The compactness criterion in l_={x( · )l^∞(0,∞))_t→∞x(t)=x(∞)} is given and as an application, we study the existence of positive solutions of second order boundary value problems of difference equation on the half line by the fixed-point theorem in cones.